Perspektif Mahasiswa STIE Perbanas Surabaya atas Tax Evasion - - Supriyati (Universitas Trunojoyo Madura, 2017)
State revenue comes from taxes currently occupies the largest portion of Revenue and Expenditure Budget (APBN). Various reforms have been undertaken by the Government in improving state revenue target. On the other hand, the taxpayer also thinks to minimize tax payments with the tax evasion. Tax evasion has been perceived as unethical because it violates the provisions of the existing taxation. This perception is influenced by factors justice, tax administration system, discrimination and Machiavellian. This is a quantitative research with the data collected from distributing questionnaires directly to the students of Bachelor of Accounting Perbanas Surabaya who are taking courses Tax Planning odd semester of 2015-2016. There were 183 respondents. Testing in this research using regression test. The results showed that the only the variable Machiavellian affects the perception of the ethics on tax evasion. Students perceived that tax evasion is an unethical act. This condition also supported their perception because they have not had experience in fulfillment of tax compliance, tax provisions normative or something that should be adhered to and support ethics courses and softskill development is done. Pendapatan negara yang berasal dari pajak saat ini memiliki porsi terbesar dalam APBN. Berbagai reformasi perpajakan telah dilakukan oleh pemerintah dalam meningkatkan target pendapatan. Di sisi lain, wajib pajak juga berpikir untuk meminimalkan pembayaran pajaknya melalui penggelapan pajak. Penggelapan pajak dipersepsikan sebagai hal yang tidak etis karena dinilai menciderai peraturan perpajakan yang telah ada. Persepsi tersebut dipengaruhi oleh faktor keadilan, sistem administrasi perpajakan, diskriminasi, dan aliran Machiavellian. Penelitian kuantitatif ini menggunakan kuesioner yang disampaikan kepada mahasiswa Akuntansi di Perbanas Surabaya yang telah menempuh mata kuliah Perencanaan Pajak pada tahun ajaran 2015/2016. Terdapat 183 responden. Pengujian hipotesis menggunakan analisis regresi. Hasil analisis menunjukkan bahwa hanya variabel Machiavellian yang berpengaruh terhadap persepsi etis dalam penggelapan pajak. Mahasiswa menilai bahwa penggelapan pajak adalah tindakan yang tidak etis. Kondisi tersebut juga didukung oleh persepsi mereka yang belum mengalami kewajiban membayar pajak.